A Co(ii)-catalyzed asymmetric ring opening reaction of spiro-epoxyoxindoles with allylboron. Issue 6 (27th February 2020) - Wu, Liang; Shao, Qihang; Kong, Li; Chen, Jianzhong; Wei, Quhao; Zhang, Wanbin
Abstract : A Co(ii )/BOX-catalyzed asymmetric allylation of spiroepoxyoxindoles was developed, which is the first stereoconvergent allylation of epoxides, yielding chiral oxindoles bearing quaternary stereocenters. Abstract : Stereoconvergent reactions of epoxides are challenging and very limited. Herein, we report the first stereoconvergent ring opening allylation of epoxides, which was catalysed by a Co(ii )/bisoxazoline catalyst, to realize the reaction between spiroepoxyoxindoles and potassium allyltrifluoroborate. This catalytic system can tolerate a wide range of spiroepoxyoxindoles. The desired chiral oxindoles bearing quaternary stereocenters could be prepared with yields of 64–90% and enantioselectivities of 57–78%. A gram-scale reaction showed the practical applicability of this enantioselective catalysis. Furthermore, preliminary mechanistic studies indicate that this reaction proceeds via a sequential epoxide-ring-opening and enantioselective addition process.